Differences in the perception of parenting styles between adolescents and their mothers - Tiongson, Idabel D.; Trio, Consuelo Q. (2004.)
The present study used the survey to determine if there are differences on the perception of adolescents and their mothers in terms of parenting styles. The study also examined if there are differences in the perception of male and female adolescents in relation to their mother's parenting styles, and if age and gender influence the differences in the perception of adolescents. Lastly, it looked into the differences on the parenting styles of the mothers towards male and female adolescents. The participants consisted of one hundred high school students, and their respective mothers, totaling to 200 respondents. Twenty-five students per year level (First - Fourth Year) participated, with equal number of boys and girls. The respondents answered an eighteen-item parenting style questionnaire. Questionnaires of adolescents and their mothers were identical with each other and differ only in the verb-pronoun usage. The study produced significant difference on the perception of adolescents and their mothers in relation to parenting styles. However, there was no significant difference on the parenting style of mothers towards male and female adolescents. Furthermore, the study revealed evidence on the influence of year level in the perception of adolescents about their mothers' parenting styles but showed no indications on the influence in the perception of adolescents. The study provided recommendations for future researches on the area of parenting styles and presented suggestions on how to conduct the survey efficiently and effectively.
Thesis (BSHE)--University of the Philippines Diliman.
Keywords: Parenting -- Philippines; Mother and daughter -- Philippines